(untitled) (Journal of Economic Research & Business Administration, 2016)
Article is devoted to justification of author’s approach to the organization of the research devoted to an assessment of influence of national factors on development of management in the Republic of Kazakhstan. The reasons forcing the researcher to develop own original concept of the analysis are shown. The main tendencies of development of modern management proving that this scientific discipline is at a paradigm shift stage are listed. Critical evaluations of the Kazakhstan authors of practice of management and their opinion concerning prospects of development of national model of management are generalized. The problems of research of influence of national factors on development of the Kazakhstan management connected with incompleteness of formation of national model, with absence of unity, eclecticism of systems of management in the Kazakhstan companies are shown. The author’s concept of the solution of these problems is formulated: the algorithm, methods and requirements to establishment of borders of research is defined. The hypothesis concerning an opportunity upon transition is stated to new paradigms of management of overcoming of a fragmentariness at an assessment of national factors of management within the offered concept